Asian Insfastructure Investment Bank (AIIB) Sebagai Bentuk Hegemoni Baru Tiongkok - Fanny, Cindy Rezma; Arifianti, Dwi Nur; Augusta, Erlandi Daffa (Nation State: Journal of International Studies, 2019)
Since the rise of China as a 'great power' in the 1940s, China has continued to expand its economic power. His role which was felt to be insignificant in the world multilateral institutions or Bretton-Woods institutions made China initiate a new multilateral institution which was considered to have a bureaucracy that was easier than the Bretton-Woods institution. In addition, the financial condition of the World Bank which is considered inadequate for the Asian infrastructure development needs and the failure of America to host China so that the American allies want to join the AIIB make China more convinced by its decision to establish AIIB. AIIB initiated by President Xi Jinping and announced its establishment in 2014. In 2015, 57 founding countries officially signed the Article of Agreement (AOA) as the basis for the formation of the AIIB. In this study, the researcher will explain the motivations behind the formation of the AIIB. This research explained through a quantitative descriptive method so that the researcher will explain the purpose of establishing AIIB in detail. As a result, by analyzing through the perspective of Dependency Theory, the dependence of third world countries on the AIIB would indirectly bring about hegemony from China.